The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1143/jjap.35.6528
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics of Fluorocarbon Radicals in a Large-area Permanent Magnet Electron Cyclotron Resonance Etching Plasma

Abstract: Diagnostics of fluorocarbon radicals and fluorine (F) atom species in a size-scaleable large-area permanent magnet electron cyclotron resonance (ECR) etching plasma employing CF4 and C4F8 gases are carried out. Non-intrusive infrared laser diode absorption spectroscopy and actinometric measurement techniques are used in evaluating the performance of the permanent magnet ECR plasma source and in studying the kinetic processes associated with etching plasma chemistry. Successful measurements of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The absolute densities of O atoms produced in plasma processes have been reported by many investigators [20][21][22][23][24][25][26][27][28]. The O-atom densities obtained in plasma processes are generally higher than that obtained in this study.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The absolute densities of O atoms produced in plasma processes have been reported by many investigators [20][21][22][23][24][25][26][27][28]. The O-atom densities obtained in plasma processes are generally higher than that obtained in this study.…”
Section: Discussionsupporting
confidence: 58%
“…The O-atom densities obtained in plasma processes are generally higher than that obtained in this study. Especially, high-density O atoms have been observed in microwave discharges and the decomposition efficiency of O 2 can be as high as 30%, which corresponds to the O-atom density of the order of 10 15 cm −3 [20,24]. The O-atom density in catalytic decomposition may be increased by one order by using a larger chamber and a longer filament.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in a previous report that such low T e values produce low energy controlled dissociation kinetics compared to conventional electromagnet ECR plasma sources. 15 The techniques used to measure the absolute densities of ground state CF x (xϭ1-3͒ and fluorine species are IRLAS and actinometry, respectively. By actinometry, the fluorine atom density was estimated using the relationship 19 n F ϭ0.56n Ar ͑ I F * /I Ar * ͒ ͑1͒…”
Section: Methodsmentioning
confidence: 99%
“…3,14 In our previous article, the diagnostics of fluorocarbon radicals and fluorine atom species in a large-area permanent magnet electron cyclotron resonance ͑ECR͒ etching plasma employing CF 4 and C 4 F 8 gases was carried out. 15 It was demonstrated that for C 4 F 8 ECR plasma, the CF 2 /F and CF/F density ratios are larger than those for CF 4 ECR plasma which implies greater selectivity. However, further investigation of the C 4 F 8 ECR plasma kinetics, which can be directly related to SiO 2 /Si etch selectivity, needs to be carried out and the main precursor species still remains very much a debated point.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of mixing H 2 to CF 4 are known to enhance selectivity of SiO 2 /Si etching. For achieving this phenomena with a single gas, several fluorocarbon compounds with hydrogen have been examined by many researchers [61][62][63][64], in which most of the discussion are based on gas phase diagnostics. In this subsection, FTIR PMSE observation of Si surfaces treated with CHF 3 plasma is demonstrated.…”
Section: Chf 3 Plasma On C-simentioning
confidence: 99%